Improving confidence and competence of healthcare professionals in end-of-life care: an evaluation of the 'Transforming End of Life Care' course at an acute hospital trust. Issue 2 (22nd November 2015) - Selman, Lucy; Robinson, Vicky; Klass, Lara; Khan, Shaheen; George, Rob; Shepherd, Kate; Burman, Rachel; Koffman, Jonathan
Abstract : Background: UK policymakers, clinicians and public wish to see improvements in end-of-life care (EoLC). However, healthcare professionals' skills and knowledge to deliver high-quality care are often lacking. Since May 2012, palliative care staff in an inner-city tertiary hospital have run a 2-day Transforming End of Life Care (TEoLC) course to improve EoLC confidence, and competence among hospital and community staff. Aim: To evaluate course participants' self-rated confidence, competence and knowledge of EoLC topics. Evaluation design: A before-and-after design using self-completion questionnaires, precourse and postcourse. 14 self-assessment questions examined confidence, understanding and knowledge of EoLC topics. Mean change scores and paired t tests were calculated and free-text responses analysed thematically. Participants: 236 staff members completed the course between May 2012 and April 2014. 42% worked in hospitals and 55% in the community; the most frequent staff roles were qualified nurses (49%), senior nurses (16%) and general practitioners (15%). Results: All 14 self-assessment topics improved significantly (p<0.001); most improved was 'understanding and implementing Fast Track discharge'. Qualitative data showed increased knowledge and confidence in EoLC, particularly in communication, commitment to team work and holistic care. Overall, 217 (92%) participants would recommend the course and 215 (98%) indicated it would influence their practice. Conclusions: The TEoLC course improved participants' self-rated confidence, competence and knowledge in EoLC. Findings have utility beyond the UK in light of the international policy recommendations to improve the palliative care skills of generalist healthcare providers.